Infant of a diabetic mother: clinical presentation, diagnosis and treatment - Magdalena Suda-Całus; Katarzyna Dąbrowska; Ewa Gulczyńska (Pediatric Endocrinology, Diabetes and Metabolism)
An infant of a diabetic mother is defined as a newborn born to a mother who has diabetes during pregnancy. The term diabetic mother refers to pregnant women with diabetes diagnosed either before (type 1 or 2 diabetes) or during pregnancy (gestational diabetes). Rising incidence of type 1 and type 2 diabetes in young women and increasing maternal age at conception account for the higher risk of birth complications and adverse maternal and infant outcomes. Infants of diabetic mothers (IDMs) because of mother’s diabetes are prone to developing complications and the most common include: large birth weight and complications resulting from it (i.e. birth injuries, perinatal asphyxia), cardiovascular and respiratory insufficiency (poor tolerance of labor stress), neonatal hypoglycemia and it’s complications, delayed lung maturity (fetal hyperinsulinism and the opposite function of insulin to cortisol), cardiomegaly and hypertrophy of the intraventricular septum (functional narrowing of the outflow of the left ventricle and cardiac failure), congenital malformations (most often of the central nervous system and heart). Less common complications in IDMs are: persistent pulmonary hypertension, hyperbilirubinemia, renal vein thrombosis, small left colon syndrome, intrauterine death, polycythemia, and a predisposition to obesity, insulin resistance and diabetes later in life. This article presents current knowledge about pathological conditions and the recommended management for IDMs.